Jesus : a very short introduction - Bauckham, Richard (Oxford : New York : Oxford University Press, 2011)
Bauckham shows that Jesus was devoted to the God of Israel, with a special focus on God's fatherly love and compassion, and like every Jewish teacher he expounded the Torah, but did so in his own distinctive way.
Includes bibliographical references (p. 115-119) and index.
Keywords: Jesus Christ -- Biography; Jesus Christ -- Person and offices; Jesus Christ -- Person and offices